Influence of Demographic Variables on Immigrants Health Status - Md. Sayed Uddin; Adam Andani Mohammed (2020)
The aim of this empirical investigation is to assess Bangladeshi temporary migrant’s general health status in Malaysia and factors affecting their health. The study was carried out through the quantitative method. A survey was conducted among 300 Bangladeshi migrant workers from construction, manufacturing and service sectors. The result indicates that the Bangladeshi temporary migrant workers reported positive self-reported health status with percentages good, very good and excellent. It was also found that the construction and service sector workers reported slightly better health status than manufacturing workers. Result showed that married workers have more health problems than singles. In addition, the low level of education creates more health problems among Bangladeshi workers. It was found that highly educated Bangladeshi workers are more likely to safeguard a sound health status. This study suggest considering Bangladeshi immigrants’ health behaviours, health status and health needs, there should be early health promotion and necessary prevention and/or intervention to improve their health conditions.